Studi Efikasi dan Keamanan Ekstrak Akar dan Daun Calotropis gigantea Terhadap Sel Kanker Kolon dan Sel Kanker Payudara Secara In Vitro - Mutiah, Roihatul (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2017)
Development of phytopharmaca for cancer until now has become a major step in overcoming the failure of cancer therapy. Calotrophis gigantea is one of the scientifically proven plants both in vitro and in vivo as a chemopreventive agent. This study aims to explain the efficacy and safety of Calotropis gigantea leaf extract (EDCG) and Calotropis gigantea root extract (EACG) on NIH3T3 cell, colon cancer cell WiDr and T47D breast cancer cells. From the analysis of MTT and Selectivity Index (SI) analysis showed that ethanol extract of leaf Calotropis gigantea (EDCG) can inhibit selective growth of selective colon cancer cells (SI 3) but not selective in inhibiting the growth of breast cancer cells T47D (SI 3 ). Calotropic gigantea (EACG) root ethanol extract is not selective in inhibiting the growth of colon cancer cells WiDr and breast cancer cells T47D (SI 3). Therefore EDCG can be recommended as a Phytopharmaca candidate with further proof through clinical trials.